Epiphyte-phorophyte relationships: assessing the differences between Seasonal Semideciduous and Swamp Forests in Southeastern Brazil1 - Marcusso, Gabriel Mendes (2019)
ABSTRACT Vascular epiphytes are responsible for a considerable portion of tropical biodiversity; however, the variation of epiphytes-phorophytes relationships in different vegetation types are still poorly understood. In this study, we aimed to assess the presence, abundance, vertical distribution, and life cycle (holoepiphyte and hemiepiphyte) of vascular epiphytes in two vegetation types [Seasonal Semideciduous Forest (- SSF), and Swamp Forest (- SF)] in order to determine any correlation with phorophyte size (diameter and height) and the specificity of phorophyte species to the epiphytic colonization. There was a higher number of phorophytes in SF; however, epiphytes density did not differ between the vegetation types. The recorded vertical distribution also showed different patterns: in the SSF, most epiphytes were found in the canopy, while in the SF they occurred mainly on the trunks of the trees. The abundance of epiphytes was positively correlated with the phorophyte size in the two vegetation types. In the SSF, colonization of phorophytes by epiphytes appeared to be less species-specific than in the SF, where trees density is likely to be a more significant factor to epiphytic colonization. The results showed the importance of the forest heterogeneity in the conservation and maintenance of vascular epiphytes assemblage, demonstrated by differences in the abundance and distribution of the epiphytes, even in contiguous forests.